Effects of Radiofrequency Electromagnetic Field (RF-EMF) exposure on male fertility and pregnancy and birth outcomes: Protocols for a systematic review of experimental studies in non-human mammals and in human sperm exposed in vitro. (December 2021) - Pacchierotti, Francesca; Ardoino, Lucia; Benassi, Barbara; Consales, Claudia; Cordelli, Eugenia; Eleuteri, Patrizia; Marino, Carmela; Sciortino, Maurizio; Brinkworth, Martin H.; Chen, Guangdi; McNamee, James P.; Wood, Andrew William; et al.
Highlights: Male infertility and adverse pregnancy outcomes are relevant human health problems. Radiofrequency electromagnetic fields are widespread in the human environment. A link between radiofrequency and adverse reproductive outcomes is controversial. This is the protocol of WHO-funded systematic review and meta -analysis on this issue. Abstract: Background: Radiofrequency Electromagnetic Fields (RF-EMF) at environmental level have been reported to induce adverse effects on the male reproductive system and developing embryos. However, despite the number of experiments conducted since the 1970s, the diversity of testing approaches and exposure conditions, inconsistencies among results, and dosimetric flaws have not yet permitted a solid assessment of the relationship between RF-EMF exposure and such effects, warranting a more systematic and methodologically rigorous approach to the evaluation of available data. Objectives: This study aims at evaluating the effects of RF-EMF exposure on male fertility and pregnancy outcomes by a systematic review (SR) of experimental studies, conducted in compliance with international guidelines. The evidence will be organized into three streams: 1) Studies evaluating the impact of RF-EMF on the male reproductive system of experimental mammals; 2) studies evaluating the impact of RF-EMF on human sperm exposed in vitro ; 3) studies evaluating the impact of RF-EMF on adverse pregnancy, birth outcomes and delayed effects in experimental mammals exposed in utero . Study eligibility and criteria: Eligible studies will include peer-reviewed articles reporting of original results about effects of controlled exposures to RF-EMF in the frequency range 100 kHz–300 GHz on the selected outcomes without any language or year-of-publication restrictions. Eligible studies will be retrieved by calibrated search strings applied to three electronic databases, PubMed, Scopus and EMF Portal and by manual search of the list of references of included papers and published reviews. Study appraisal and synthesis method: The internal validity of the studies will be evaluated using the Risk of Bias (RoB) Rating Tool developed by National Toxicology Program/Office of Health Assessment and Translation (NTP/OHAT) integrated with input from the SYRCLE RoB tool. Given sufficient commensurate data, meta -analyses will be performed, otherwise narrative syntheses will be produced. Finally, the certainty of the effects of RF-EMF exposure on male fertility and pregnancy and birth outcomes will be established following GRADE. Funding: The study is financially supported by the World Health Organization. Registration: OSF Registration DOI https://doi.org/10.17605/OSF.IO/7MUS3 ; PROSPERO CRD42021227729, CRD42021227746.